If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h = -16t + 70t + 9 Reorder the terms: h = 9 + -16t + 70t Combine like terms: -16t + 70t = 54t h = 9 + 54t Solving h = 9 + 54t Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Simplifying h = 9 + 54t
| -18+20x=2 | | 2.5y=55 | | 9x/2=-18 | | 4n/5-7/11=53/55 | | x/9-1=2 | | (m^2-9)/(m^2-6m+9) | | 8x-20=4x-4 | | 7=3x+6 | | 20=4x+20 | | 4/6-2=6 | | 8w+7=31 | | 11(z+2)-3(z-3)=4(2-3)+3(z-1) | | y=14-(5x-8) | | -19=-5x+12 | | -15=-4n+5 | | x^3+12x^2-3x-910=0 | | 10x-91=-107 | | 240-12x+x*x=0 | | 17x-(8x-4)=13 | | 5/6y=-20 | | -3x/8=-3 | | 2(5z+2)-6=88 | | (5x/8y^3)^2 | | x+24.8=48.5 | | 5(5x-1)=100 | | 40-2x=-38 | | 4x+9x-6x=42+7 | | 23=8x-9 | | 8-3n=n+4 | | -15x-60=-120 | | 10r+4=104 | | 0r+4=104 |